Smart Home Controlling and Monitoring System using Multiboard Client-Server Internet of Things (IoT) - T P Zuhelmi; S R Sulistiyanti; F X A Setyawan; A R Adnan (Journal of Engineering and Scientific Research, 2019)
An increasing number of crimes in society make people want to take advantage of technological developments to improve their safety and comfort. This paper research the possibilities to make house secure and comfort by using internet of things (IoT) to control and monitor also well known as smart house. This paper using NodeMCU ESP-12E for the IoT controller and smartphone for user to control and monitor house environment. The results shows that the system designs for smart home are promising. The sensors response time for average response time is 2.52 seconds for solenoid door lock, the average responses time for motion detection testing is 2.30 seconds, the average response time for first lamp is 3.71 seconds and 4.37 seconds for second lamp, the average response time is 1.74 seconds for LPG gas leakage, the average response time is 2.59 seconds for front terrace and 2.17 seconds for back terrace.